Photoredox Trifluoromethylation/Cyclization of N-Arylacrylamides with 4-(Difluoroamino)-1-[(trifluoromethyl)sulfonyl]pyridinium Triflate (TFSP) - Sun, Zetian; Yang, Hui; Chen, Huimin; Mao, Fenghua; Li, Xiaoqing; Xu, Xiangsheng (Synlett, 2023)
A photoredox trifluoromethylation/cyclization of N-arylacrylamides with inexpensive stable solid 4-(difluoroamino)-1-[(trifluoromethyl)sulfonyl]pyridinium triflate (TFSP) has been developed.
Keywords: trifluoromethylation; cyclization; arylacrylamides; photoredox reaction; indolones